Dampak Globalisasi Terhadap Kesenjangan Sosial Sektor Pendidikan di Indonesia - Arya Indy Putra; Al Muhtadi Billah; Satria Tata Wijaya; Faisal Ariq (Empat Sembilan Publisher, 2025)
Globalisation has a significant impact on the education sector in Indonesia, particularly in terms of social inequality and the quality of education. In the context of social inequality, globalisation exacerbates disparities in access to education between urban and rural areas, as well as among different economic groups. The challenge of equitable education becomes more complex due to differences in quality, relevance, and efficiency. Education in some regions is often not aligned with global market needs and is frequently inefficient in delivering knowledge. Therefore, globalisation necessitates reforms in the education system to make it more inclusive, high-quality, and relevant to contemporary challenges.